2020
DOI: 10.1111/ppc.12446
|View full text |Cite
|
Sign up to set email alerts
|

A study on the relationship between perceptions of successful aging and life satisfaction of Turkish elderly people

Abstract: Purpose: In the current study, the relationship between perceptions of successful aging and the life satisfaction of Turkish elderly people was investigated.Design and Methods: This cross-sectional study was conducted with 561 elderly people at a public hospital.Findings: The mean scores of the participating elderly people obtained from the Successful Aging Scale (54.34 ± 11.55) and Satisfaction with Life Scale (3.46 ± 1.01) were high, and there was a significant positive correlation (r = 0.305) between them.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The mean score of older adults participating in the study obtained from the LSS was 12.99 ± 3.708. This result is lower than the life satisfaction levels of older adults determined in many studies conducted in Turkey during the pre‐pandemic period 39–43 . However, in studies conducted in Turkey during the pandemic, it has been demonstrated that life satisfaction and quality of life levels of older adults decreased due to the concern of Coronavirus disease, 43–46 which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The mean score of older adults participating in the study obtained from the LSS was 12.99 ± 3.708. This result is lower than the life satisfaction levels of older adults determined in many studies conducted in Turkey during the pre‐pandemic period 39–43 . However, in studies conducted in Turkey during the pandemic, it has been demonstrated that life satisfaction and quality of life levels of older adults decreased due to the concern of Coronavirus disease, 43–46 which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Although death is inevitable, being able to derive meaning from painful experiences can speed up focus and help individuals deal with problems. 11 In this process, individuals constantly question the meaning of life, their expectations from life, their capacity to cope with life's challenges and their ability to connect with those who are close to them. Given that old age affects an individual's life purpose and plans, rearranging the individual's life goals and expectations is thus necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of an individual is to lead a meaningful life. Although death is inevitable, being able to derive meaning from painful experiences can speed up focus and help individuals deal with problems 11 . In this process, individuals constantly question the meaning of life, their expectations from life, their capacity to cope with life's challenges and their ability to connect with those who are close to them.…”
Section: Introductionmentioning
confidence: 99%
“…These resources can also help older adults achieve their personal goals and meet the basic physical and psychological needs [ 10 ]. Considering that life satisfaction is considered as a subjective concept that assesses several dimensions including health, psychological, and social in older people’s life, it could be an indispensable part of successful aging [ 11 ]. Therefore, the evaluation of social, psychological and health factors could have pivotal role for achieving successful aging.…”
Section: Introductionmentioning
confidence: 99%